2008
DOI: 10.1177/0363546507312643
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Coracoclavicular Stabilization with Suture Anchors for Acute Acromioclavicular Dislocation

Abstract: This minimally invasive technique using a suture anchor for the treatment of acute AC dislocation is easily performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 18 publications
1
46
1
3
Order By: Relevance
“…12,14 An important fact in this study is the large number of cases with increase of the coracoclavicular distance observed in the postoperative period, higher than those found in literature for the treatment of AAD with suture anchors. 12,14 In patient number 20, submitted to revision of the surgical procedure, and in the five other patients initially excluded from the study due to loss of the AAD reduction 15 days postoperatively (which were also submitted to revision of the surgical procedure), it was observed that the reduction loss was related to rupture of the wire used in the eyelet of the anchor, not having any connection to the loosening of the suture anchor of the coracoid process or with its poor positioning. We understand that the wire ruptured due to wear and tear in its passage through the suture anchor eyelet, where the wire is submitted to considerable tension force in a small contact area.…”
Section: 19mentioning
confidence: 65%
See 3 more Smart Citations
“…12,14 An important fact in this study is the large number of cases with increase of the coracoclavicular distance observed in the postoperative period, higher than those found in literature for the treatment of AAD with suture anchors. 12,14 In patient number 20, submitted to revision of the surgical procedure, and in the five other patients initially excluded from the study due to loss of the AAD reduction 15 days postoperatively (which were also submitted to revision of the surgical procedure), it was observed that the reduction loss was related to rupture of the wire used in the eyelet of the anchor, not having any connection to the loosening of the suture anchor of the coracoid process or with its poor positioning. We understand that the wire ruptured due to wear and tear in its passage through the suture anchor eyelet, where the wire is submitted to considerable tension force in a small contact area.…”
Section: 19mentioning
confidence: 65%
“…Notwithstanding the diversity of available techniques, as described above, this study focused on the stabilization technique between clavicle and coracoid process, particularly with the use of metallic anchors, which we shall now analyze here. The stabilization technique between clavicle and coracoid process with the subcoracoid ligation technique, through endobuttons or anchors, has been described by several authors [6][7][8][9][10]12 with satisfactory results. It has the advantage of not requiring removal of the synthesis material, besides having proven effective in the reestablishment and maintenance of AC joint reduction.…”
Section: 19mentioning
confidence: 99%
See 2 more Smart Citations
“…4,7 These studies demonstrated superior outcomes for high-grade injuries treated surgically. Additional controversy exists as to the best surgical technique among over 70 different described procedures [4,[9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%